Perspective: Vitamin D supplementation prevents rickets and acute respiratory infections when given as daily maintenance but not as intermittent bolus: Implications for COVID-19 - Kenny, Rose (My University, 2021)
The value of vitamin D supplementation in the treatment or prevention of various conditions is often viewed with scepticism as a result of contradictory results of randomised trials. It is now becoming apparent that there is a pattern to these inconsistencies. A recent large trial has shown that high-dose intermittent bolus vitamin D therapy is ineffective at preventing rickets – the condition that is most unequivocally caused by vitamin D deficiency. There is a plausible biological explanation since high-dose bolus replacement induces long-term expression of the catabolic enzyme 24-hydroxylase and fibroblast growth factor 23, both of which have vitamin D inactivating effects. Meta-analyses of vitamin D supplementation in prevention of acute respiratory infection and trials in tuberculosis and other conditions also support efficacy of low dose daily maintenance rather than intermittent bolus dosing. This is particularly relevant during the current COVID-19 pandemic given the well-documented associations between COVID-19 risk and vitamin D deficiency. We would urge that clinicians take note of these findings and give strong support to widespread use of daily vitamin D supplementation.
PUBLISHED
cited By 0
Keywords: COVID‐19; Dosing; Efficacy; Maintenance; Vitamin D; Ageing